Case report on unusual tumor with synchronous cutaneous and gastrointestinal tract involvement - Raj, Aditi; Gaikwad, Vaishali; Amarapurkar, Anjali (International Journal of Health Sciences, 2021)
Histiocytic sarcoma (HS) is an exceedingly rare lymphohematopoietic malignancy with morphological and immunophenotypic characteristics of mature tissue histiocytes. We report a unique case of a HS with synchronous skin and gastrointestinal tract involvement which has not been reported in literature till date to the best of our knowledge. A 70-year-old male farmer presented with multiple ulcerated skin lesions ranging from 0.5 to 10 cm all over the body. Autopsy revealed multiple transmural nodular deposits in stomach, intestines, head of pancreas, and peripancreatic tissue. Histopathology and immunohistochemistry profile was consistent with HS exhibiting positivity for CD68, CD163, and lysozyme. CD 163 identifies histiocytic malignancies with high degree of specificity and has become a promising marker for their diagnosis.